2016
DOI: 10.1097/01.xme.0000481469.56478.b0
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis and psychiatric comorbidities

Abstract: BackgroundMyasthenia gravis (MG) is a chronic, autoimmune disease involving neuromuscular junctions frequently associated with psychiatric morbidity in terms of depression and anxiety. The interaction between MG and psychiatric disorders needs to be appreciated, especially in the primary care setting, as the symptoms may overlap. The main objective of this study was to recognize the rate of occurrence of psychiatric morbidity among MG patients and to assess the demographic variations of patients and its releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…The study demonstrated a statistically significant correlation between the prevalence of depression and the severity of the disease. This result corresponds with the results of other studies [35,47,48,50]. At the baseline of our evaluation, in the group of MG patients with depression and antidepressive treatment, the MG-ADL score was 7.73 (SD = 5.05), while in the group of MG patients without the diagnosis of depression, the MG-ADL score was 4.30 (SD = 4.84, p < 0.001), a statistically significant difference.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The study demonstrated a statistically significant correlation between the prevalence of depression and the severity of the disease. This result corresponds with the results of other studies [35,47,48,50]. At the baseline of our evaluation, in the group of MG patients with depression and antidepressive treatment, the MG-ADL score was 7.73 (SD = 5.05), while in the group of MG patients without the diagnosis of depression, the MG-ADL score was 4.30 (SD = 4.84, p < 0.001), a statistically significant difference.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of our study suggest that individuals with myasthenia gravis who received treatment with antidepressants tend to be younger, with a mean age of 42.27 years (SD = 14.88), than patients without depression, 58.97 years (SD = 14.67, p < 0.001), and with a shorter duration of illness, the first group had a mean duration of illness of 59.55 months (SD = 66.98) compared to 95.03 months (SD = 102.64, p = 0.023) in the group of MG patients without depression. This statement supports the underlying premise that the etiology of psychiatric morbidity can be attributed to MG's persistent and debilitating nature, resulting in limitations across several domains of life [35], diminished quality of life, and significant psychological distress [44]. Additionally, the fluctuating symptoms of myasthenia gravis and the possibility of a myasthenia crisis contribute to increased irritability, tension, and anxiety in patients, increasing their susceptibility to depressive and anxiety disorders [45].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation